Effect of Instruction Program on Nurses’ Knowledge about Reducing Fear and Anxiety Related to Nursing Intervention among Children: فاعليه البرنامج الارشادي في معارف الممرضين تجاه تقليل قلق وخوف الاطفال اثناء التداخلات التمريضية - Hammed, Yasser; Ghafel, Hawraa Hussein (Iraqi National Journal of Nursing Specialties, 2026)
Objective(s): Evaluating nurses' knowledge towards reducing children's anxiety and fear during nursing interventions, determining the effectiveness of the Instructional Program on nurses' knowledge towards reducing children's anxiety and fear during nursing interventions. Methods: The study was designed as a Quiz-experimental design (test-retest approach) for study group participants employed in the (Fatima Al Zahraa Hospital for Maternal and Child care ) and( Ibn Al Baladi Hospital for in pediatric emergency unit and pediatric medical units .(30)of them were the  study group and (30)of them were the control group . The study was started at December 15, 2022 to April 25, 2023. Results: The results of the study showed nurses level of knowledge about reducing children's anxiety and fear during nursing interventions for the study sample and the control sample were fair   in the pre-test time (76.7%, M±SD= 6.97 ± 1.810), while they are showing a good level of knowledge during the post-test 1 (100%, M±SD= 10.83 ± .379) and post-test 2 (100%, M±SD= 1070 ± .702). Conclusion: The counseling program, after its application, had a positive and effective effect on the nurses' knowledge towards reducing children's anxiety and fear during nursing interventions. Recommendations: The study recommended nurses need training courses to reduce children's anxiety and fear during nursing interventions. Nurses need training courses to reduce children's anxiety and fear during nursing interventions.